PENGARUH DEMAND SUPPLY DAN ENVIRONMENT TERHADAP PERILAKU STOP BABS DI KABUPATEN BANGLI - Gusti Ayu Aryasih (Jurnal Skala Husada : The Journal of Health, 2017)
Abstract[A1]  The success STBM program involves three main components, namely Demand, suply and Environment where success is one of the targets of Conduct Stop open defecation. The study aims to determine the effect of demand, supply and enveronment against Stop open defecation behavior in Bangli by selecting a survey method. The sample was selected randomly composed of people who have been exposed to triggers. Analysis using Chi - Square with a significance level of 0.05. The results showed no significant effect on the behavior of demand Stop open defecation: p (0.116) α (0.05), there is significant influence between the supply of the stop open defecation behavior with: p (0.001) α (0.05) and the value of OR = 9.6. There is a significant influence of environment on stop open defecation behavior: p (0.006) α (0.05) and the value of OR = 11.205. It is recommended that the person in charge of the program continue to implement the integration of the components of demand, supply and the environment with more considering the factors of supply and the environment, choose the method of assistance is appropriate and gives understanding to the community that the program STBM is a self-help program is purely non subsidies and provide technology introduction latrine simple and inexpensive so economic limitation is not an excuse to not have it healthy for society. Keywords: Demand; provision; Environment: Stop Open Defecation.  Abstrak. Keberhasilan program STBM melibatkan tiga komponen pokok yaitu Demand, Suply dan Environment dimana salah satu target keberhasilannya adalah Perilaku Stop BABS. Penelitian bertujuan mengetahui pengaruh demand, supply dan enveronment terhadap perilaku Stop BABS  di Kabupaten Bangli dengan memilih metode survei. Sampel dipilih secara random yang terdiri dari masyarakat yang sudah pernah terpapar pemicuan. Analisis menggunakan Uji  Chi - Square dengan derajat kemaknaan 0,05. Hasil menunjukkan tidak ada pengaruh signifikan antara demand terhadap perilaku Stop BABS: p (0,116) α (0,05), terdapat pengaruh signifikan antara supply  terhadap perilaku Stop BABS dengan: p (0,001) α (0,05) dan  nilai  OR = 9,6. Terdapat pengaruh signifikan environment terhadap perilaku Stop BABS  :p (0,006) α (0,05) dan nilai  OR = 11,205. Disarankan agar penanggung jawab program  tetap melaksanakan  keterpaduan komponen demand, supply dan environment dengan lebih mempertimbangkan faktor supply dan environment,  memilih metode pendampingan yang tepat dan memberi pemahaman kepada masyarakat bahwa program STBM adalah program swadaya murni bukan subsidi dan memberikan pengenalan teknologi jamban sederhana dan murah sehingga keterbatasan ekonomi tidak dijadikan alasan untuk tidak memiliki jamban sehat bagi masyarakat.Kata kunci  :  Permintaan; Penyediaan; Lingkungan: Tidak BABS [A1]Jadikan 250 kata